Metaphors of eucharistic presence : language, cognition, and the body and blood of Christ / Stephen R. Shaver. - Shaver, Stephen R. (Oxford University Press, 2022)
"One of the most challenging questions for Christian ecumenical theology is how the relationship between the eucharistic bread and wine and Jesus Christ's body and blood can be appropriately described. This book takes a new approach to controverted questions of eucharistic presence by drawing on cognitive linguistics. Arguing that human cognition is grounded in sensorimotor experience and that phenomena such as metaphor and conceptual blending are basic building blocks of thought, the book proposes that inherited models of eucharistic presence are not necessarily mutually exclusive but can serve as complementary members of a shared ecumenical repertoire. The central element of this repertoire is the motif of identity, grounded in the Synoptic and Pauline institution narratives. The book argues that the statement "The eucharistic bread and wine are the body and blood of Christ" can be understood both as figurative and as true in the proper sense, thus resolving a church-dividing dichotomy. The identity motif is complemented by four major non-scriptural motifs: representation, change, containment, and conduit. Each motif with its entailments is explored in depth and suggestions for ecumenical reconciliation in both doctrine and practices are offered. The book also provides an introduction to cognitive linguistics and offers suggestions for further reading in that field"--